Development, validity and reliability of Place-Based Process Genre Module (PBPGM) - Abd Halib Mohd Ali; Suyansah Swanto; Wardatul Akmam Din; Jacinta Karen Juin (Global Academic Excellence, 2021)
The present study is a Type 1 design and developmental research (DDR) study that aims to analyse the situation, design, develop and evaluate an instructional Place-Based Process Genre Module (PBPGM). Upon completing the needs analysis, design and development of the module, it underwent a pilot test. The validity and reliability were then conducted. A panel of experts were involved in determining the validity of the module's content, sessions, and activities. A group of 30 ESL learners were involved in determining its reliability. All content, sessions and activities were rated above 70%, and all sessions and activities were rated over alpha value of 0.70 indicating that PBPGM was valid and reliable to be experimented with.